An Experimental Study on the Effects of Reciprocal and Inquiry Teaching Styles on Physical Education Students' Learning Outcomes for Butterfly Swimming Technique, FKIP UNCEN - Zainal Widyanto; Andi Syaiful; Marsuki Marsuki; Heppy Hein Wainggai (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. This study investigates the effectiveness of Reciprocal and Inquiry teaching styles as alternative models to improve Butterfly swimming style learning. Materials and Methods. The method used is an experimental method using a Pre-test Post-test Control Group Design, in this design the sample is obtained as large as the population size, and then an initial test or pre-test is held. The population in this study was 90 Physical Education and Physical Education students from the Faculty of Teacher Training and Education, Cenderawasih University. The sampling technique in this research used a purposive sampling technique, with a total sample of 30 people who were divided into two groups, which are the group with the reciprocal teaching method and the group with the inquiry method using matching with ordinal pairing. Results. The research findings indicate that both reciprocal teaching style and inquiry teaching style have a positive impact on improving the learning outcomes of butterfly swimming for students of UNCEN FKIP Penjaskesrek. The reciprocal teaching style achieved a t-count of 9.44 and a t-table of 2.201, while the inquiry teaching style had a t-count of 4.34 and a t-table of 2.201. Conclusion. The reciprocal teaching style is more effective than other teaching styles in improving butterfly swimming learning outcomes for Physical Education students at FKIP UNCEN.